"Growth-Promoting Effect" of Antibiotic Use Could Explain the Global Obesity Pandemic: A European Survey - Gábor Ternák; Márton Németh; Martin Rozanovic; Gergely Márovics; Lajos Bogár (MDPI AG, 2022)
Clinical observations indicated a higher rate of obesity among children who received antibiotics at early ages. Experimental studies supported the role of the modified gut microbiome in the development of obesity as well. For identifying antibiotic classes that might promote or inhibit obesity-related dysbiosis, a database of the average yearly antibiotic consumption (2008-2018) has been developed using the European Center for Disease Prevention and Control (ECDC) yearly reports of antibiotic consumption in the community for the major antibiotic classes in 30 European countries, which were compared to the childhood and adult obesity prevalence featured in the Obesity Atlas. Pearson's chi-square test was applied to estimate positive/negative correlations between antibiotic consumption and obesity. One-way ANOVA has been applied to test the differences in antibiotic consumption between groups, and logistic regression analysis was performed to determine the odds ratios (OR) of antibiotic consumption for obesity. Strong, positive associations were estimated between childhood obesity and the total consumption of systemic antibiotics, broad-spectrum, beta-lactamase-resistant penicillin, cephalosporin, and quinolone, and a negative correlation was found with the consumption of tetracycline, broad-spectrum, beta-lactamase-sensitive penicillin, and narrow-spectrum, beta-lactamase-sensitive penicillin. Our observation indicated that the "growth-promoting effect" of the consumption of certain antibiotic classes might be identified as a possible etiology in the development of obesity and might be the explanation for the obesity "pandemic".